The economic-social policy of resilient development and common prosperity in the construction of new development paradigm and Rural Revitalisation. Issue 3 (2nd September 2022) - Wang, Sibin
ABSTRACT: Rural Revitalisation is an important part of the construction of the new development paradigm. In this context, the revitalisation and development of rural areas in the central and western regions need economic-social policies for resilience development. It is an economic and social policy focusing on Rural Revitalisation, which can promote rural resilient development with the purpose of promoting rural economic development, boosting rural popularity and raising the level of economic and social life in rural areas. It is a policy group, including the revitalisation and development of county economy, the implementation of economic policies conducive to social development, the implementation of public policies and social policies, and the mechanism of enabling them integrative development. All the above eventually contributes to the development of common prosperity of the rural.